Sauce Nativo - Amico, Ivana Lourdes; Gallo, Leonardo Ariel; De Durana, Federico Guillermo; Garcia Cortes, Manuel; Mikuc, Juan Pablo; Martinez, Abel Hector Maria (EEA Valle Inferior, INTA, 2023)
EEA Esquel